Strategi Penginjilan Kontekstual Rasul Paulus Berdasarkan 1 Korintus 9:19-27 - Pasa, Iskandar Dinata; Andi Yusuf, Etni Grace (Sekolah Tinggi Teologi Berita Hidup, 2024)
In the era of disruption, contextual evangelism is always needed as a model of approach for preaching the gospel. This article aims to study the Apostle Paul's contextual evangelism strategy in Corinth based on 1 Corinthians 9:19-27. Contextual can be interpreted as a persuasive approach in preaching the gospel that can be accepted according to the local context. Using a descriptive qualitative method, the author analyzes how the Apostle Paul's contextual service strategy in the city of Corinth is based on 1 Corinthians 9:19-27. The author collects various information using a literature approach and applies the principle of hermeneutics through an exegetical approach to the keywords contained in the text. Based on the analysis carried out, it is concluded that the Apostle Paul used several strategies in carrying out contextual evangelism in the city of Corinth. The strategies used are: interactive dialogue, evangelism by identifying culture, and lifestyle evangelism.Dalam era disrupsi, penginjilan kontekstual senantiasa diperlukan sebagai model pendekatan bagi pemberitaan Injil. Artikel ini bertujuan untuk mempelajari strategi penginjilan kontekstual Rasul Paulus di Korintus berdasarkan 1 Korintus 9:19-27. Kontekstual dapat diartikan pendekatan secara persuasif dalam pemberitaan Injil yang dapat diterima sesuai konteks setempat. Dengan menggunakan metode kualitatif deskriptif, penulis menganalisa bagaimana strategi pelayanan kontekstual Rasul Paulus di kota Korintus berdasarkan 1 Korintus 9:19-27. Penulis mengumpulkan berbagai informasi dengan menggunakan pendekatan literatur dan menerapkan prinsip hermeneutika melalui pendekatan eksegesa terhadap kata-kata kunci yang terdapat dalam teks. Berdasarkan analisa yang dilakukan diperoleh kesimpulan bahwa Rasul Paulus menggunakan beberapa strategi dalam melaksanakan penginjilan kontekstual di Kota Korintus. Strategi yang digunakan adalah: dialog interaktif, penginjilan dengan melakukan indentifikasi budaya, dan penginjilan gaya hidup.